2021
DOI: 10.30773/pi.2020.0208
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress, Positive Resources and Their Interactions as Possible Related Factors for Depressive Symptoms

Abstract: Objective The present study aimed to explore how the patterns of interaction between stress and positive resources differ according to the severity of depression and which resources play the most important role among the various positive resources.Methods The study included 1,806 people who had visited a health screening center for a mental health check-up to evaluate the levels of perceived stress, positive resources, and depressive symptoms. The participants were divided into a depressive group (n=1,642, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In the current study, positive psychological resources were assessed using the Positive Resources Test (POREST), a self-reported instrument for assessing optimism, purpose/hope, self-control, social support, and care ( 18 ). The POREST consists of 23 items, and participants provide their responses on a five-point Likert scale ranging from 1 (not true) to 5 (very true).…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, positive psychological resources were assessed using the Positive Resources Test (POREST), a self-reported instrument for assessing optimism, purpose/hope, self-control, social support, and care ( 18 ). The POREST consists of 23 items, and participants provide their responses on a five-point Likert scale ranging from 1 (not true) to 5 (very true).…”
Section: Methodsmentioning
confidence: 99%
“…The POREST showed good consistency (Cronbach’s alpha 0.80 for optimism, 0.80 for purpose/hope, 0.67 for self-control, 0.70 for social support, and 0.82 for care) in a study of the impact of interaction patterns between stress and positive resources on depression symptoms in Korea. 26 …”
Section: Methodsmentioning
confidence: 99%
“…Perceived stress, which refers to an individual's perceptions or ideas about the levels of stress they experience at a given time or during a specified period, can affect various aspects of the individual's life 28 . Previous studies have shown that perceived stress is a predetermined psychological state that occurs before experiencing depressive symptoms 29,30 . Individuals with high levels of perceived stress are often distressed; thus, they are likely to experience depressive symptoms 31 .…”
Section: The Mediating Role Of Perceived Stressmentioning
confidence: 99%
“…28 Previous studies have shown that perceived stress is a predetermined psychological state that occurs before experiencing depressive symptoms. 29,30 Individuals with high levels of perceived stress are often distressed; thus, they are likely to experience depressive symptoms. 31 Moreover, it has been reported that perceived stress is a complicated cognitive appraisal process influenced by many factors, and the most important factor may be the stressor.…”
Section: The Mediating Role Of Perceived Stressmentioning
confidence: 99%